TDIC no ensino de língua inglesa: possibilidades na educação de surdos - Almeida, Matheus Lucas de (2021)
Digital Information and Communication Technologies (DICT) are making tons of changes in our society nowadays. It shows that research on issues related to teaching and learning should have special attention on this process. In this context, there is also an inclusive movement that seeks to welcome the different, bringing to the classroom students who have different needs, whether physical, psychological, or linguistic. Taking these factors into account, we analyze here the contributions of DICT to the teaching of English as an additional language to the deaf. We also identify technological tools and propose methodologies for teaching the written modality of English to these individuals. Besides, we develop an educational material with didactic suggestions for teaching English to the deaf mediated by technologies. For this, the research has a qualitative approach of action research and follows Triviños (2010), Burns (2015), and Paiva's (2019) guidelines. Johnson (2004), Vygotsky (1981, 1998), Bakhtin/Volochinov (2006), Bakhtin (1986, 2016), Moraes (2012, 2015, 2018), Figueiredo (2019), Paiva (2014, 2019), Sousa (2014, 2018) among others help to support our theoretical framework. We have collected the data with the support of an online questionnaire answered by 10 participants from different states in brazil, who were English teachers and, or interpreters of Brazilian sign language with experience in teaching/interpreting the English language to deaf students. The questionnaire questions addressed issues related to their work conditions, the ways of coping observed in their work environment, and the methodological possibilities that may be used with deaf students. For data analysis, we adopted the Content Analysis proposed by Bardin (2009). The results indicate that teaching the English language to the deaf, mediated by technologies, may obtain satisfactory results. However, some specificities need to be respected and considered.